2017
DOI: 10.21475/ajcs.17.11.11.pne573
|View full text |Cite
|
Sign up to set email alerts
|

Productive characteristics of quinoa (Chenopodium quinoa Willd.) under irrigation and potassium fertilization

Abstract: Quinoa (Chenopodium quinoa Willd.) quickly adapts to different climatic conditions; however, low soil fertility conditions and inadequate soil water levels may reduce yield. The objective of this study was to evaluate the effect of irrigation levels and potassium fertilization for quinoa production in the Cerrado Oxisol. The experiment was performed in a greenhouse, located at the Federal University of Mato Grosso (UFMT), Campus of Rondonópolis -Brazil, using soil collected from a Cerrado Oxisol. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In the red river delta in Vietnam, under normal and saline stress conditions of an alluvium soil, the growth parameters, and yield components increased according to the increase of the N application rates from 0 to 90 kg N ha -1 , then decreased when the nitrogen rates were higher (Dinh et al, 2015(Dinh et al, , 2021. Conducting a green-house experiment, Rêgo et al (2017) found linear correlations of K application rate with the shoot and root dry mass, but polynomial correlations with the number of grain and grain production in quinoa. The grain yield of quinoa increased significantly when the K application rate was raised up to 120 kg ha -1 , then slightly decreased by the application at the rate of 180 kg ha -1 (Salim et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…In the red river delta in Vietnam, under normal and saline stress conditions of an alluvium soil, the growth parameters, and yield components increased according to the increase of the N application rates from 0 to 90 kg N ha -1 , then decreased when the nitrogen rates were higher (Dinh et al, 2015(Dinh et al, , 2021. Conducting a green-house experiment, Rêgo et al (2017) found linear correlations of K application rate with the shoot and root dry mass, but polynomial correlations with the number of grain and grain production in quinoa. The grain yield of quinoa increased significantly when the K application rate was raised up to 120 kg ha -1 , then slightly decreased by the application at the rate of 180 kg ha -1 (Salim et al, 2019).…”
Section: Discussionmentioning
confidence: 97%